Fast Calculation of Supercritical Carbon Dioxide Flow, Heat Transfer Performance, and Mass Flow Rate Matching Optimization of Printed Circuit Heat Exchangers Used as Recuperators - Kun Xi; Zhihui Xie; Xiang Zhao; Yu Song; Hanyu Liu (Mathematics, 2023)
Printed circuit heat exchangers (PCHEs) are widely used as recuperators in the supercritical carbon dioxide (S-CO2) Brayton cycle design. The variation of heat sources will have a great impact on the heat transfer effect of the recuperator. It is of interest to study the fast calculation of flow and heat transfer performance of PCHEs under different operating conditions to obtain the optimal comprehensive performance and provide guidance for the operation control strategy analysis. Herein, a fast calculation method is established through a one-dimensional model of a PCHE based on Modelica. The effects of working medium mass flow rate and inlet temperature on the flow and heat transfer process are analyzed from the three aspects of heat transfer rate, flow pressure drop, and comprehensive performance, and the mass flow rate matching optimization is realized. The results show that increased mass flow rate increases heat transfer rate and flow pressure drop. The efficiency evaluation coefficient (EEC) has a maximum value at which the mass flow rate values of the cold and hot channels are best matched, and the comprehensive performance is optimal. When the mass flow rate of the heat channel is 4.8 g/s, the maximum EEC is 1.42, corresponding to the mass flow rate of the cold channel, 4.2 g/s. Compared with the design condition, the heat transfer rate increases by 62.1%, and the total pump power increases by 14.2%. When the cold channel inlet temperature increases, EEC decreases rapidly, whereas EEC increases when the hot channel inlet temperature increases. The conclusions can provide theoretical support for the design and operation of PCHEs.